Relevansi Undang-Undang Tindak Pidana Pencucian Uang Dalam Menghadapi Kejahatan Pencucian Uang Di Era Digital - Alfa Syahda; EVi Deliana HZ; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Money laundering crimes are included as white-collar crimes because theprocess of this crime is generally not carried out by ordinary people, but byintellectuals, bureaucrats, corporates, officials, politicians and criminal actorswho rely more on intellectual abilities. In writing, the author focuses on therelevance of the Law on Money Laundering in the Face of Money LaunderingCrimes in the Digital Age. The purpose of writing this thesis is first to find out therelevance of the law on money laundering in dealing with patterns of moneylaundering crimes in the current digital era. The second is to find out the idealarrangement for money laundering crimes in dealing with money launderingcrimes in today's digital era.The author conducted research using normative juridical methods orliterature studies in order to obtain secondary data through documentary studies,namely by studying and analyzing descriptively comparative laws and regulationswith theories that have a relationship to the problems studied.From the research results, there are two main things that can be concluded.First, Law no. 8 of 2010 concerning the Prevention and Eradication of MoneyLaundering Crimes has not explicitly regulated the tracking and confiscation ofthe assets of the predicate crime as well as the proceeds of money launderingusing Cryptocurrency facilities, the second is the Ideal Arrangement for MoneyLaundering Crimes in the Face of Crime Money Laundering in the Digital Era Itis necessary to reconstruct Indonesian Criminal Law by including, among otherthings, the confiscation and confiscation of proceeds and instruments of crime ina law.The author's suggestion, in this study, is to suggest that Law EnforcementOfficials (APH) make improvements to Law Number 8 of 2010 on restrictions onnon-criminal money laundering by adding rules related to money launderingwhich is carried out using digital currencies such as cryptocurrencies andcurrencies. other digital services so that law enforcement against moneylaundering crimes in this digital era can provide legal certainty.Keywords: Crime, Money Laundering, Digital Era